2017
DOI: 10.1289/ehp659
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Salinity and Raised Blood Pressure: Evidence from a Cohort Study in Coastal Bangladesh

Abstract: Background:Millions of coastal inhabitants in Southeast Asia have been experiencing increasing sodium concentrations in their drinking-water sources, likely partially due to climate change. High (dietary) sodium intake has convincingly been proven to increase risk of hypertension; it remains unknown, however, whether consumption of sodium in drinking water could have similar effects on health.Objectives:We present the results of a cohort study in which we assessed the effects of drinking-water sodium (DWS) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 35 publications
(45 reference statements)
2
70
0
2
Order By: Relevance
“…over 3000 mg/L. The high groundwater salinities dictate local inhabitants to rely on less saline ponds, canals, rivers, etc., as alternative water sources (Benneyworth et al 2016;Islam et al 2013;Khan et al 2011;Scheelbeek et al 2017;Worland et al 2015). It also means that use of the groundwater for irrigation is relatively low compared to other parts of the country.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…over 3000 mg/L. The high groundwater salinities dictate local inhabitants to rely on less saline ponds, canals, rivers, etc., as alternative water sources (Benneyworth et al 2016;Islam et al 2013;Khan et al 2011;Scheelbeek et al 2017;Worland et al 2015). It also means that use of the groundwater for irrigation is relatively low compared to other parts of the country.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…In 2014, this association was again confirmed in a case-control study that measured sodium levels in household drinking water sources and found that women consuming tube well (groundwater) were at higher disease risk than those drinking rainwater; a dose response relationship between salinity and both pre-eclampsia and gestational hypertension was reported (Khan et al 2014). Since then, three studies have also linked drinking water salinity and blood pressure among a small sample of the general population (Scheelbeek et al 2016), among young adults (Talukder et al 2016), and a survey of the general population through the Assessing Health, Livelihoods, Ecosystem Services and Poverty Alleviation in Populous Deltas (ESPA Deltas) project (Nahian et al 2018). Another study detected a link between drinking water salinity and infant mortality using Demographic and Health Survey (DHS) data (Dasgupta et al 2015).…”
Section: Coastal Bangladesh and Pe/ementioning
confidence: 99%
“…Groundwater typically contains higher sodium levels than surface water. A recent study found mean sodium concentrations in drinking water in coastal Bangladesh of 700 mg/L, in some areas exceeding 1500 mg/L; the WHO recommends a maximum sodium intake of 2000 mg that can be easily exceeded in this region between dietary salt intake and drinking water (Scheelbeek et al 2016). Approximately 20 million people live in coastal areas of Bangladesh affected by varying degrees of salinity in drinking water (MOEF 2006).…”
Section: Coastal Bangladesh and Pe/ementioning
confidence: 99%
“…However, seawater intrusion has resulted in salinity-induced water scarcity in southwest coastal regions of Bangladesh 10 . Epidemiological studies from southwest coastal Bangladesh have found positive associations of drinking saline water with sodium (Na) intake, blood pressure, and with hypertensive disorders of pregnant women (e.g., preeclampsia) [11][12][13][14] . To address water salinity problems, rainwater-harvesting systems and pond sand filters near rainwater-fed ponds are currently being promoted in southwest coastal Bangladesh 15,16 .…”
Section: Introductionmentioning
confidence: 99%